SURGERY FOR ADULT SPINAL SCOLIOSIS: DO THE BENEFITS OUTWEIGH THE RISKS? - DEDÉA,JEFERSON (2019)
ABSTRACT Around 6% of the elderly population over 65 years of age are affected by adult spinal deformity (ASD). The increasing prevalence of ASD with aging has prompted discussion regarding the use of various techniques for its treatment, such as surgery and conservative treatment. The objective of this study is to investigate whether surgical treatment demonstrates significant benefits as compared to conservative treatment. A literature review was conducted, focusing on the most relevant papers on the topic published in the last five years. Surgical treatment, which costs an average of US$ 99,114 per procedure, enables almost instant improvement of the pain and disability of ASD. The rate of perioperative complications in ASD is approximately 7.5%, and the average improvement in back pain is 6.2 times higher in the surgical approach than in conservative treatment. In addition, the use of modern operative techniques, such as minimally invasive surgery (MIS), reduces the complications and greatly improves patients’ quality of life, compared to open surgery. Therefore, the expected benefits of surgical treatment meets the patient’s expectations by eliminating the pain caused by ASD. Although surgical treatment has a higher cost and a greater risk of complications, the use of minimally invasive techniques give the ASD patient a better quality of life. Level of evidence III; Non-Systematic Review.